TERJEMAHAN KOLOKASI AL-QUR’AN DEPAG - Sriana Sriana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2020)
The Indonesian Ministry of Religion collocation translation published in 1965 requires an additional touch of meaning and more explanation, so that it is easily understood by the target reader represented by two languages ​​namely the meaning of the collocation of the source language of the Qur'an that is not a cultural product, so that it follows the steps of analysis using semantics al-Qur'an developed by Toshihiko Izutsu. Al-Qur'an semantics according to Izutsu is an attempt to reveal the world view of the Qur'an (weltanschauung) through semantic analysis of vocabulary or key terms of the Qur'an.